Ultrasound-assisted intravesical botulinum toxin A delivery attenuates acetic acid—induced bladder hyperactivity in rats - Liu, Qinggang; Gao, Yi; Cong, Huiling; Liao, Limin (Frontiers in Pharmacology, 2023)
Background: Intradetrusor injection of botulinum toxin A (BTX-A) is an effective treatment for overactive bladder (OAB). However, the occurrence of adverse events associated with BTX-A injection therapy hinders its acceptance among patients and its clinical promotion. Intravesical instillation of BTX-A offers a promising alternative to injection therapy for treating OAB. Nevertheless, due to the presence of the bladder permeability barrier (BPB) and the high molecular weight of BTX-A, direct instillation is unable to penetrate the bladder urothelium. Purpose: This study aims to investigate the safety and feasibility of ultrasound-assisted intravesical delivery of BTX-A and its potential benefits in a rat model of bladder hyperactivity induced by acetic acid instillation. Methods: Hengli BTX-A and microbubbles (MB) were mixed and prepared as a novel complex. The size distribution and zeta potentials of the complex were measured. On day 1, rats' bladders were instilled with 1 mL of saline, BTX-A (20 U in 1 mL), MB, or MB-BTX-A (20 U in 1 mL) complex with or without ultrasound (US) exposure (1 MHz, 1.5 W/cm2, 50% duty cycle, sonication for 10 seconds with a 10-second pause for a total of 10 minutes). The instillations were maintained for 30 minutes. After seven days, cystometry was performed by filling the bladder with saline and 0.3% acetic acid (AA). Bladders were collected, weighed, and processed for immunoblotting, enzyme-linked immunosorbent assay (ELISA), histologic, and immunofluorescence analyses. Results: Intercontraction intervals (ICI) decreased by 72.99%, 76.16%, and 73.96% in rats pretreated with saline, BTX-A, and US+MB, respectively. However, rats treated with US+MB+BTX-A showed a significantly reduced response to AA instillation (57.31% decrease in ICI) without affecting amplitude, baseline pressure, or threshold pressure. Rats treated with US+MB+BTX-A exhibited increased cleavage of SNAP-25 and CGRP expression compared to the control group. Conclusions: Ultrasound-assisted intravesical delivery of BTX-A, with the assistance of MB cavitation, led to cleavage of SNAP-25, inhibition of calcitonin gene-related peptide release from afferent nerve terminals, and amelioration of acetic acid-induced bladder hyperactivity. These results support ultrasound-assisted intravesical delivery as an efficient non-injection method for administering BTX-A.